(untitled) (Sustainability in Debate, 2013)
The Ecological Footprint (EF) is configured as an indicator of sustainability and quality of life, well as an environmental accounting methodology which assesses the pressure from human consumption of natural resources. The EF of a person, city or country is given by the area of productive land or sea required to sustain their lifestyle, which involves food, housing, transportation, among others. In this paper was calculated the EF of Campo Grande city, which resulted in 3,03 global hectares of productive land per capita, needed to sustain their lifestyle. Were considered to calculate the EF variables: green area; built urban areas; areas of illegal occupation; beef consumption; food consumption; emission produced by burning fossil fuels; electricity consumption; water consumption and waste production. The EF was 12,22% above the global EF and 68,33% above what is considered affordable for every inhabitant of the planet.